Newly identified energy levels and calculated transition rates in astatine atom, the rarest element on Earth. (January 2018) - Quinet, Pascal; Sicorello, Guillaume
Highlights: A detailed investigation of the atomic structure of At I is presented. Spectroscopic designations are given for some experimentally observed energy levels. Newly identified energy levels in 6p 4 7p, 6p 4 9p and 6p 4 10p configurations are reported. Level energies along the 6p 4 np and 6p 4 nd Rydberg series are predicted. The influence of intravalence, core-valence and core-core electron correlation is discussed. Abstract: A theoretical investigation of the atomic structure and radiative parameters involving the lowest states within the 6p 5, 6p 4 7s and 6p 4 7p configurations of neutral astatine is reported for the first time in the present paper. Using different physical models based on the pseudo-relativistic Hartree–Fock approach, the influence of intravalence, core-valence and core-core electron correlation on the atomic parameters is discussed in detail. This work allowed us to establish the intermediate-coupling composition and to clearly fix the spectroscopic designation of six excited levels within the 6p 4 7s and 6p 4 7p configurations which had been located in previous experimental studies. In addition new tentative identifications of four levels belonging to the 6p 4 9p and 6p 4 10p configurations are reported in this work together with predicted level energies along the 6p 4 n p and 6p 4 n d Rydberg series up to n = 50.